Response of the Polar Urals glaciers to the modern climate changes - G. A. Nosenko; A. Ya. Muraviev; M. N. Ivanov; A. I. Sinitsky; V. O. Kobelev; S. A. Nikitin (Лëд и снег, 2020)
Monitoring of glacier mass balance is usually focused on analysis of middle and large glaciers, so small glaciers on the verge of extinction remain out of the attention of researchers. Studies of glaciers of the Polar Urals, begun in the mid-twentieth century, present in this respect interesting information. The series of observations of them is the longest among other glaciers of the mountainous regions of the Russian mainland in the polar latitudes. New results of quantitative assessment of changes in the size and mass balance of glaciers in this region are presented. To estimate the geodetic balance of the IGAN Glacier, data from photogeodetic surveys of 1963, data of ground-based DGPS surveys of 2008 and 2018 together with a fragment of the digital elevation model (DEM) of the ArcticDEM v3.0 of 2016 were used. Using these data, the DEM of its surface was calculated as of 1963, 2008, and 2018, and the changes in the glacier volume were estimated for the period from 1963 to 2018, during which the glacier had lost 19.7 million m3 of ice, of which 3.2 million m3 were lost in the last decade. The average decrease in the surface height was 18.94±3.22 m, and the maximum – 53.5±1.0 m. In 1963–2008, the specific massbalance was equal to −317±59 mm w.e./year, while in 2008–2018 −336±61 mm/year. Estimation of changes in the size of 30 glaciers of the Polar Urals made from images of the Sentinel-2 satellite had shown that in 2000– 2018 the glaciers lost 2.02 km2 (about 28%) of the area. In comparison with the period of 1953–2000, the average annual rate of reduction of their area doubled and amounted to 0.112 km2/year (1.54%/year). Magnitudes of the reduction of individual glaciers are not identical. Within the selection of 30 glaciers, they vary from 7.1% (the Terentyev Glacier) to 61.1% (the Oleniy Glacier). The analysis of changes in temperature and precipitation in 2000–2018 allows us making the conclusion that the reason for the accelerated reduction of glaciers in the Polar Urals in these years is the rise of summer air temperature since beginning of the twentieth century by 1.5 °C, to which the lowering of winter precipitation was added in the last decade.